Bank Specific Factors on the Financial Performance of Commercial Banks in Nepal - Dhodary, Shanker; Rajbanshi, Prem Lal (NCC Journal, 2024)
Purpose-This study examines the bank-specific factors and financial performance of commercial banks in Nepal. The study period of Nepalese banks’ performance during a period ranging from 2013 to 2023. Design/methodology/approach- Descriptive research design has been used in analyzing the performance of commercial banks. Banks’ performance is measured in terms of ROA, ROE, and NIM. Profitability has been taken as the proxy of performance of banks in this study. Based on the findings of the study. Findings- Nepali commercial banks are performing moderately. They are not able to increase their performance level significantly. Their performance measured in terms of profitability is not very satisfactory. However, observing the significant decrease in level of non-performing assets, it is concluded that the internal management, credit policy, and business management aspects of the Nepalese commercial banks have been improving. On the other hand, Nepalese commercial banks are well-capitalized and do not have solvency problems. Because of maintaining an adequate capital adequacy ratio, they have the capacity to absorb unexpected losses and safeguard the depositors, investors and creditors. Original/Value- Few studies have addressed the interplay of microfinance on poverty alleviation in Nepali context.